2015
DOI: 10.1007/s11695-014-1513-6
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality-of-Life (HRQoL) on an Average of 12 Years After Gastric Bypass Surgery

Abstract: Long-term follow-up after GBP for morbid obesity showed better scores in most aspects of HRQoL compared to obese controls but did not achieve the levels of the general population. Patients with better medical outcome after gastric bypass operation had better HRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
54
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 22 publications
13
54
0
3
Order By: Relevance
“…In a cross-sectional analysis, Sanchez-Santos et al 37 reported that a smaller percentage of adults at least 5 years after RYGB (22% [50]) had difficulty with mobility when compared with controls matched on presurgery characteristics (55%; P < .01). Likewise, Raoof et al 38 reported that mean (SD) scores for bodily pain and physical function on the SF-36 were better 12 (3) years post-RYGB when compared with those of morbidly obese controls who were awaiting surgery (matched on age and sex). Another study, 39 which provided follow-up for 145 LAGB patients for 3 to 8 years, reported that fewer patients had significant knee pain at follow-up vs baseline (38% vs 47%; P < .01).…”
Section: Discussionmentioning
confidence: 98%
“…In a cross-sectional analysis, Sanchez-Santos et al 37 reported that a smaller percentage of adults at least 5 years after RYGB (22% [50]) had difficulty with mobility when compared with controls matched on presurgery characteristics (55%; P < .01). Likewise, Raoof et al 38 reported that mean (SD) scores for bodily pain and physical function on the SF-36 were better 12 (3) years post-RYGB when compared with those of morbidly obese controls who were awaiting surgery (matched on age and sex). Another study, 39 which provided follow-up for 145 LAGB patients for 3 to 8 years, reported that fewer patients had significant knee pain at follow-up vs baseline (38% vs 47%; P < .01).…”
Section: Discussionmentioning
confidence: 98%
“…The authors postulated that this finding may be attributed to a decreased absorption in patients with LRYGB, but the exact mechanism of this is also not known [22]. Bariatric surgery remains the most effective treatment for patients with severe obesity because of the excellent weight loss results and rates of co-morbidities resolution in the general population [12][13][14][15]. These benefits, however, have Heart Ejection fraction before LSG Ejection fraction after LSG 10 55% 65%…”
Section: Discussionmentioning
confidence: 99%
“…It is known to provide significant and sustained weight loss [12], improvement in quality of life [13], remission of obesity-related diseases [14,15] and reduced mortality [16] in most patients in the general population. Bariatric surgery has been shown to be safe and effective before organ transplantation [17] in addition to improving candidacy in obese patients awaiting transplantation [18,19].…”
mentioning
confidence: 99%
“…Beyond survival effects, another important consideration is the improvement in quality of life (QOL) that can be achieved after bariatric surgery. Improved mobility and reductions in obesityrelated co-morbidity medications offer an opportunity for significant improvement in QOL in this population, and this is another area for further research [35,36].…”
Section: Discussionmentioning
confidence: 99%